2010
DOI: 10.1159/000245644
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peripheral Ultrafiltration in the Management of Acute Decompensated Heart Failure

Abstract: Heart failure is a common and highly morbid condition associated with recurrent hospitalizations for disease decompensation. As such, heart failure is a growing public health concern from both a utilization and cost perspective. The current standard of care for the management of volume overload symptoms is underpinned by a diuretic-based treatment regimen. There is now increasing data to suggest that this approach may be counterproductive and result in progression of cardiac and renal disease with resultant hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Ultrafiltration as an alternative method is used to improve volume overload symptoms in all subsets of HF patients, including those with diuretic resistance or renal insufficiency [57]. The ability to precisely control the removal of sodium and water allows the ultrafiltrate extracted from serum during UF therapy to be isotonic.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafiltration as an alternative method is used to improve volume overload symptoms in all subsets of HF patients, including those with diuretic resistance or renal insufficiency [57]. The ability to precisely control the removal of sodium and water allows the ultrafiltrate extracted from serum during UF therapy to be isotonic.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the chronic complications, acute decompensated heart failure and a finding of volume overload may necessitate rapid treatment approaches [2]. Diuretics are a good choice of treatment and may be of benefit to certain patients under acute conditions, but if there are findings of excess fluid overload like respiratory distress, UF can be the only choice of treatment for a life-saving procedure [3,4,5]. A recent study by Bart et al [6 ]concluded that the use of an algorithm with steps of pharmacological therapy was superior to a strategy of UF for the protection of renal function on day 4 of treatment, and that UF was associated with higher rates of side effects.…”
mentioning
confidence: 99%